Analisis Faktor Internal Yang Mempengaruhi Kinerja Usaha Peternakan Ayam Petelur Di Kecamatan Penebel, Kabupaten Tabanan: Analisis Faktor Internal Yang Mempengaruhi Kinerja Usaha Peternakan Ayam Petelur Di Kecamatan Penebel, Kabupaten Tabanan - Sahatmana, Gede Wisnu; Darmawan, Dwi Putra (Universitas Duta Bangsa Surakarta, 2025)
This study aims to analyze the influence of entrepreneurship, innovation, financial management, and farmers' capacity on the business performance of layer poultry farms in Penebel District, Tabanan Regency. The research was conducted in three main villages: Babahan, Senganan, and Jatiluwih, which are the centers of layer poultry farming in the region. The analytical method used was Generalized Structured Component Analysis (GSCA) with a saturated sampling technique involving 51 farmers. The results indicate that entrepreneurship, innovation, financial management, and farmers' capacity do not have a significant effect on business performance. This is mainly due to the influence of external factors such as fluctuations in feed and egg prices, as well as the farmers' position as price takers in the market. Therefore, empowering farmers and implementing supportive policies are necessary to optimize the development of layer poultry farming businesses.